2023
DOI: 10.1371/journal.pbio.3002367
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide regulates cholesterol levels through SREBP2

Nityanand Bolshette,
Saar Ezagouri,
Vaishnavi Dandavate
et al.

Abstract: In mammals, O2 and CO2 levels are tightly regulated and are altered under various pathological conditions. While the molecular mechanisms that participate in O2 sensing are well characterized, little is known regarding the signaling pathways that participate in CO2 signaling and adaptation. Here, we show that CO2 levels control a distinct cellular transcriptional response that differs from mere pH changes. Unexpectedly, we discovered that CO2 regulates the expression of cholesterogenic genes in a SREBP2-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…Another recent study [5] reported low O 2 (hypoxia) shuts down the SREBP2 pathway by promoting the ubiquitination and degradation of this transcription factor (TF). However, here the mechanism is very different since Bolshette and colleagues [2] found low CO 2 did not affect SREBP2 stability, but rather, low CO 2 activates SREBP2 target genes by reducing cholesterol in the ER. Accordingly, Bolshette and colleagues [2] found that further depleting cell cholesterol by using cyclodextrin blunted the effect of low CO 2 .…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Another recent study [5] reported low O 2 (hypoxia) shuts down the SREBP2 pathway by promoting the ubiquitination and degradation of this transcription factor (TF). However, here the mechanism is very different since Bolshette and colleagues [2] found low CO 2 did not affect SREBP2 stability, but rather, low CO 2 activates SREBP2 target genes by reducing cholesterol in the ER. Accordingly, Bolshette and colleagues [2] found that further depleting cell cholesterol by using cyclodextrin blunted the effect of low CO 2 .…”
mentioning
confidence: 67%
“…Given the centrality of CO 2 to our metabolism, perhaps it is not surprising roles are emerging for this previously dismissed waste product in key metabolic pathways, including those involving cholesterol. In this issue of PLOS Biology [2], Bolshette and colleagues link CO 2 levels to the master transcriptional regulator of cholesterol homeostasis, Sterol Regulatory Element Binding Protein-2 (SREBP2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Metacore transcription factor analysis revealed a notable conservation of interactions between several transcription factors, including AML1, SOX17, TAL1, ETS1, and LMO2 ( Supplementary Table S5 ). Transcription factors previously linked with hypercapnia were also identified in our list but were not among the most prominent hits in our model, e.g., Transcription Factor P65 (RelA) [ 29 ], NFκB Subunit 2 (NFKB2) [ 22 ], Hypoxia Inducible Factor 1 Alpha (HIF1α) [ 37 ], Heat Shock Transcription Factor 1 (HSF1) [ 35 ], Cyclic AMP-Responsive Element-Binding Protein 1 (CREB) [ 38 ], Forkhead Box O3 (FOXO3a) [ 39 ], Early Growth Response 2 (EGR2) [ 40 ], Sterol Regulatory Element Binding Transcription Factor 2 (SREBP2) [ 41 ].…”
Section: Discussionmentioning
confidence: 99%